The Influence of English Competence and Work Experience on Employee Performance at PT. Samudera Indonesia, Tbk Makassar Branch - Indra, Yasmin Afifah; Abdul Wahid; Andi Hajar (International Journal of Business English and Communication, 2024)
English is a worldwide language that many countries used as the first and second language. This causes the company also participate in its use as a condition for the sustainability of the company. In line with this, experience also plays an important role in the running of a company. Experiences are things that have been passed, felt, and learned. This study aimed to determine the influence of English competence and work experience on employee performance. This research is descriptive qualitative. The research subjects were five employees of PT. Samudera Indonesia, Tbk. Makassar branch was selected using a purposive sampling technique. The results of this study signify that employee performance is influenced by English skills and work experience. The more English is used and the more experienced employees, the greater work results to affected the company needs.